2006
DOI: 10.1086/506976
|View full text |Cite
|
Sign up to set email alerts
|

Gene Flow in Complex Landscapes: Testing Multiple Hypotheses with Causal Modeling

Abstract: Predicting population-level effects of landscape change depends on identifying factors that influence population connectivity in complex landscapes. However, most putative movement corridors and barriers have not been based on empirical data. In this study, we identify factors that influence connectivity by comparing patterns of genetic similarity among 146 black bears (Ursus americanus), sampled across a 3,000-km(2) study area in northern Idaho, with 110 landscape-resistance hypotheses. Genetic similarities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
726
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 591 publications
(743 citation statements)
references
References 56 publications
10
726
2
5
Order By: Relevance
“…Although landscape genetics has certainly proven to be a robust technique for species with extensive field data (for example, Cushman et al, 2006;Shafer et al, 2012), application to poorly understood species can be difficult. Ideally, investigators should develop specific hypotheses about how landscape heterogeneity impacts gene flow in a focal species within the study area and parameterize resistance models accordingly (for example, Balkenhol et al, 2009;Anderson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although landscape genetics has certainly proven to be a robust technique for species with extensive field data (for example, Cushman et al, 2006;Shafer et al, 2012), application to poorly understood species can be difficult. Ideally, investigators should develop specific hypotheses about how landscape heterogeneity impacts gene flow in a focal species within the study area and parameterize resistance models accordingly (for example, Balkenhol et al, 2009;Anderson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, our results suggest roads do not unduly influence functional connectivity. Indeed, while previous landscape genetic studies have found roads as a limiting factor to gene flow in black bears, the relative influence of roads varies among populations (Cushman et al., 2006; Short Bull et al., 2011), and in some cases, roads may serve to facilitate rather than impede bear movement (Balkenhol & Waits, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The relative support for each model was based on the difference in the partial Mantel correlation after partialling out the resistance distance of the other model. The model with significant and positive relative support values for all comparisons was considered the best candidate model (Cushman et al., 2006, 2013). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for species that are continuously rather than patchily distributed, use of genetic data to estimate gene flow has been hampered by an inability to delineate populations. Use of individualbased measures of pairwise genetic relatedness allows for investigations of fine-scale genetic structure and dispersal patterns of continuously distributed species without a priori delineation of populations [17,18]. Pairwise relatedness represents the degree of shared ancestry, or the probability that two alleles at a locus, one taken at random from each of two individuals, are identical by descent [19].…”
Section: Introductionmentioning
confidence: 99%